Discourses of Disavowal: Gendered Anti-Blackness in State and Media Strip-Search Archives - Latty, Stephanie (Atlantis)

(untitled) (Mount Saint Vincent University, 2024)
This article undertakes a critical examination of prevailing discourses circulated by public authorities and the media during the weeks and months following three instances of Black women and girls being strip-searched by police in Canada: Audrey Smith in Toronto in 1993, three unnamed Black girls in Halifax in 1995, and Stacy Bonds in Ottawa in 2008. By focusing on three primary discourses of disavowal evident in both media accounts and legal records of these cases, this article sheds light on how collusion among the Canadian state, the criminal justice system, and the media culminate in narratives that re-install the national myth of Canada as a benevolent nation. Ultimately, the paper argues that the violence of the strip-search is naturalized through the disavowal of gendered anti-Black violence and liberal discourses of reform are upheld.